2018
DOI: 10.1016/j.bbmt.2018.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Pretransplant Multidrug-Resistant Gram-Negative Colonization in Autologous and Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Multidrug-resistant Gram-negative bacteria (MDR-GNB) are an emerging cause of morbidity and mortality after hematopoietic stem cell transplantation (HSCT). Three-hundred forty-eight consecutive patients transplanted at our hospital from July 2012 to January 2016 were screened for a pretransplant MDR-GNB colonization and evaluated for clinical outcomes. A pretransplant MDR-GNB colonization was found in 16.9% of allo-HSCT and in 9.6% of auto-HSCT recipients. Both in auto- and in allo-HSCT, carriers of a MDR-GNB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 25 publications
2
33
1
3
Order By: Relevance
“…The same has been highlighted in a multicenter study in non-HCT patients from New York as well, which is supposed to be the CRGNB epicenter of the United States [31]. Even though some studies have claimed success of early initiation of CRGNB-directed antibiotics [26], our experience has not been gratifying with a similar approach. This was primarily because the GNB species responsible for colonization and BSI were often sensitive to colistin alone or even pan-resistant.…”
Section: Discussionmentioning
confidence: 59%
“…The same has been highlighted in a multicenter study in non-HCT patients from New York as well, which is supposed to be the CRGNB epicenter of the United States [31]. Even though some studies have claimed success of early initiation of CRGNB-directed antibiotics [26], our experience has not been gratifying with a similar approach. This was primarily because the GNB species responsible for colonization and BSI were often sensitive to colistin alone or even pan-resistant.…”
Section: Discussionmentioning
confidence: 59%
“… 3 - 5 , 7 But we found that Gram-negative bacteria was the most frequent microorganisms and these data are consistent with the recently reported shift of prevalence from Gram-positive to Gram-negative bacteria in neutropenic patients malignancy. 1 , 2 , 11 Endogenous flora that contains mainly of enterobacteriaceae in the gastrointestinal tract can cause bacteremia episodes in patients with neutropenia due to a breakdown of mucosal barriers secondary to chemotherapy. 19 The reduction in the use of the central venous catheter and the reduced presence of severe mucositis may have contributed to a decreasing in Gram-positive bacteremia.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the development of intensive chemotherapy protocols and interventional procedures have resulted a serious increase in cure rates of the patients, while immunosuppression caused by these treatments also enhances incidence rates of infection. 1 , 2 The relationship between fever and infection in neutropenic patients was defined during the 1960s. Initially, this rarely encountered relationship was described as a serious clinical entity after more widespread and intensive use of cytotoxic drugs and its treatment was started thanks to developed guidelines.…”
mentioning
confidence: 99%
“…Across the haematology and oncology population, especially in the transplanted patients, MDR infections has been linked to increased intensive care unit requirements and mortality (Haeusler and Levene ). Although previous studies suggest an important role of MDR Gram‐positive bacteria, such as VRE or MRS in transplant recipients, their incidence in our cohort was lower, making the scenario as largely being dominated by Gram‐negative pathogens and thus becoming the main focus of our study (Scheich et al ; Forcina et al ).…”
Section: Discussionmentioning
confidence: 68%